Relationship between 800-m running performance and accumulated oxygen deficit in middle-distance runners - Craig, I. S.; Morgan, D. W. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: To determine whether there is a significant relationship between accumulated oxygen deficit (AOD) and 800-m running performance in a group of runners of homogeneous ability. METHODS: Nine well-trained male middle and long distance runners (age = 24.7 +/- 4.5 yr, body mass = 69.4 +/- 8.5 kg, VO2max = 64.8 +/- 4.5 mL.kg-1.min-1) underwent treadmill testing to determine maximum oxygen uptake (VO2max), running economy (RE) at 1% and 10.5% treadmill gradient, and AOD at 1% and 10.5% treadmill gradient; 800-m running performance was determined by time trials on an outdoor 440-yd track, for which the average time was 132 +/- 4 s. For the AOD test, subjects were required to run on the treadmill at supramaximal speeds until volitional exhaustion. The AOD value was calculated using linear (LIN) and curvilinear (CUR) extrapolation procedures. RESULTS: Mean AOD values using LIN and CUR were 45.0 +/- 6.9 and 59.3 +/- 10.1 mL.kg-1 at a 1% treadmill gradient and 63.2 +/- 10.6 and 93.6 +/- 19.7 mL.kg-1 at a 10.5% gradient, respectively. No significant relationship was found between 800-m run time and AOD at 1% gradient or 10.5% gradient or when AOD was estimated from a linear or curvilinear fit of the VO2 data. Other variables measured in this study (e.g., VO2max and running economy) were not found to be predictive of 800-m run time. CONCLUSION: Among a homogeneous group of well-trained male middle- and long-distance runners, AOD measured at a 1% and 10.5% treadmill gradient is not significantly related to 800-m running performance.